Effects of the Your Family, Your Neighborhood Intervention on Neighborhood Social Processes. (25th November 2019) - Brisson, Daniel; Lechuga Peña, Stephanie; Mattocks, Nicole; Plassmeyer, Mark; McCune, Sarah
Abstract: The objective of this study was to ascertain whether participation in the Your Family, Your Neighborhood (YFYN) intervention, an intervention for families living in low-income neighborhoods, leads to improved perceptions of neighborhood social cohesion and informal neighborhood social control. Fifty-two families in three low-income, urban neighborhoods participated in the manualized YFYN intervention. In this quasi-experimental study treatment families ( n = 37) in two low-income neighborhoods received YFYN and control families ( n = 15) from one separate low-income neighborhood did not. Families receiving YFYN attended 10 two-hour skills-based curriculum sessions during which they gathered for a community dinner and participated in parent- and child-specific skills-based groups. Treatment families reported increases in both neighborhood social cohesion and informal neighborhood social control after receiving YFYN. However, families receiving YFYN did not experience statistically significant improvements in perceptions of neighborhood social cohesion or informal neighborhood social control compared with nontreatment families. In conclusion, the delivery of YFYN in low-income neighborhoods may improve perceptions of neighborhood social cohesion. Further testing, with randomization and a larger sample, should be conducted to provide a more robust understanding of the impact of YFYN.